Control contable de las actividades operativas de la asociación provincial colectivo social “corazones valientes” periodo 2021. - García Ortiz, Sara Natali (2022)
Global emissions from greenhouses have been rising for years and the planet is on the verge of potentially catastrophic climate change. The emergence of COVID-19 has also shown how disastrous the consequences of ecosystem loss can be. The Provincial Social Collective Association "Brave Hearts" is an association that promotes the preparation and execution of comprehensive development plans, projects and programs. Manage the achievement of economic resources for goods and services from national and international public and private institutions that our groups require within the parameters of the Association. The organization is developed in an associative field where the primary factor is the interrelation of social microenterprises that arise from the need to obtain income through self-sustaining activities. The Ministry of Social Economic Inclusion has this study as the object of analyzing the accounting activity. This social organization, with the purpose of acquiring economic resources, serves as an intermediary between producers and the community in the commercialization of agricultural products and also the sale of seeds and grafts, especially of timber trees, with the benefits they obtain, facilitating training for the peasant sector, for which has had the contribution of the Higher Polytechnic School of the coast, Technical University of Babahoyo and the University of Los Andes -UNIANDES-. In the association they also promote the planning and execution of social, cultural, economic and productive activities aimed at the integral development of the organization.